Análisis de los mecanismos de seguridad en un ISP de nivel tres y propuesta de implementación de IPSEC en un entorno IPV6. - Gallegos Altamirano, Belén Marcela (2018)
In this paper, in the first instance, a complete analysis of the security mechanisms of a level three Internet service provider is carried out. For this, we first study some principles related to the Internet such as history, basic characteristics and statistical data, then describe what is the full operation of an ISP, as well as its structure and some protocols that are developed in this environment, also detailing the different types of ISPs that currently exist. The study of security criteria that are handled in Internet service providers is developed. This study includes the security requirements presented by this type of organization, both from the ISP point of view and from the point of view of the end user. It also describes a security model based on the computer security standard ISO / IEC 27001, which can be adopted by organizations that are dedicated to the commercialization of Internet access. As a fundamental part of this document, a proposal for the implementation of the IPSec security protocol is presented within an IPv6 environment. This proposal is managed under the mode of a network simulation performed on the Riverbed Modeler program in its academic version. The statistical data produced by this network prototype are analyzed and later presented as a sample of the viability of the proposal.